Loss of thermal refugia near equatorial range limits. (3rd November 2015) - Lima, Fernando P.; Gomes, Filipa; Seabra, Rui; Wethey, David S.; Seabra, Maria I.; Cruz, Teresa; Santos, António M.; Hilbish, Thomas J.
Abstract: This study examines the importance of thermal refugia along the majority of the geographical range of a key intertidal species ( Patella vulgata Linnaeus, 1758) on the Atlantic coast of Europe. We asked whether differences between sun‐exposed and shaded microhabitats were responsible for differences in physiological stress and ecological performance and examined the availability of refugia near equatorial range limits. Thermal differences between sun‐exposed and shaded microhabitats are consistently associated with differences in physiological performance, and the frequency of occurrence of high temperatures is most probably limiting the maximum population densities supported at any given place. Topographical complexity provides thermal refugia throughout most of the distribution range, although towards the equatorial edges the magnitude of the amelioration provided by shaded microhabitats is largely reduced. Importantly, the limiting effects of temperature, rather than being related to latitude, seem to be tightly associated with microsite variability, which therefore is likely to have profound effects on the way local populations (and consequently species) respond to climatic changes.